Effect of in vitro testicular spermatozoa culture on pregnancy outcomes: an experience at a single university hospital - Lee, Jisun (Yeungnam Univ J Med, 2020)
BACKGROUND: There are no guidelines for the optimal incubation time or temperature to improve pregnancy outcomes in testicular sperm extraction-intracytoplasmic sperm injection (TESE-ICSI) cycles. We aimed to evaluate whether a 24-hour in vitro culture of testicular spermatozoa affects pregnancy outcomes in TESE-ICSI cycles. METHODS: This was a retrospective study of 83 TESE-ICSI cycles using testicular spermatozoa in 46 couples with male partners suffering from nonobstructive or obstructive azoospermia. Sperm retrieval was performed either on the oocyte retrieval (OR) day (65 cycles in 33 couples; group A) or on the day before OR (18 cycles in 13 couples; group B) followed by in vitro culture for 24 hours. The clinical characteristics and pregnancy outcomes, including the number of retrieved oocytes, fertilization rates, embryo transfer rates, implantation and clinical pregnancy rates, were compared between the two groups. RESULTS: There were no differences in terms of clinical characteristics except for the levels of luteinizing hormone (LH) in males. Group B had higher LH levels than group A (4.56±1.24 IU/L vs. 3.67±1.07 IU/L, p=0.017). Group B showed higher fertilization rate (72.4%±32.1% vs. 59.2%±21.7%, p=0.045), implantation rate (35.0%±34.1% vs. 14.0%±21.5%, p=0.010), pregnancy rate per cycle (80% vs. 39%, p=0.033), and clinical pregnancy rate per cycle (80% vs. 37.5%, p=0.024) than those of group A. CONCLUSION: Testicular sperm retrieval performed on the day before OR followed by in vitro culture can potentially improve pregnancy outcomes.